Production and exporting process done by the tobacco company in the A.J. FERNANDEZ during the year 2013 (Revista Científica Estelí, 2015)
In this research study an evaluation of the process of production and exports done by the tobacco company in A.J. FERNANDEZ in the second half of 2013. This research is qualitative approaches in depth the process of production and exports by that company. The main recommendations for the tobacco processing company focusing on monitoring the management process in the production and export activities, as well as ensuring compliance with Good Manufacturing Practices (GMP).Keywords: Administration, exporting, production